ПОЗАМОВНА СИСТЕМА ОПЕРАТИВНОГО УПРАВЛІННЯ: ГОЛОВНІ ОСОБЛИВОСТІ ТА ОЗНАКИ - Артем’єв, В. В. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article deals with the methodology for developing a customized system of operational control under conditions of a single type of production. Firstly, considerable attention is paid to improving scheduling: a) a method of calendar coordination between technical training and basic production in the conditions of a stochastic network schedule of technical preparation is developed. The variants of the named coordination are considered, which make it possible to establish the directive dates for the beginning of the design, proceeding from the directive date for the beginning of the production of products for which the technical documentation is being developed. b) the technique of rebuilding the network calendar schedule into tape calendar schedules for the number of complete paths of the network model is presented. The named approach unites in a single volumetric-calendar space technical training with the main production behind the methods of its construction and organization of implementation. Secondly, the features of the organization of dispatching in the conditions of a single production are considered: - the main control parameter is the duration of the production cycle, as well as the duration of individual work and the network model of the design process, while in the batch production the main control parameter is the value of the start-up lot. - The main accounting document for operational accounting and control in the shops of the main production and in the technical training departments is the routing sheet. The methods of its development and main purpose are considered; - the basic volume-calendar information carrier-tool is a card file for the main production shops and technical training departments, through which the dispatch service for each current date of the reporting period establishes the state of the production system along the entire production chain. The considered improvement of dispatching serves as a basis for the information-computer control option (ICBCO) within the framework of the order-based production management system.